COMMUNITY RESPONSES OF NORTH BANDUNG SUBURBS TO LAND CONVERSION - Lili Somantri (Universitas Negeri Medan, 2021)
The northern suburbs of Bandung City are an expansion area of the development of Bandung City. The regional development in suburban areas can cause land conversion problems. The objective of the present study was to identify the community's response and the factors of land conversion in the northern suburbs of Bandung City. A descriptive quantitative method was employed through the presentation of percentages and the results of interviews with 108 respondents. Findings reveal that the people’s responses to land conversion exhibited positive and negative responses. Among the positive responses were that land conversion was perceived appropriate for regional development; road construction could increase citizen mobility and create job opportunities. Meanwhile, among the negative responses were that land conversion could result in hot temperatures, barren fields, humidity, lack of water sources, and the loss of agricultural land. The factors affecting land use conversion included population growth, the development of the Bandung City area, construction of residential and tourist areas, increased land prices, and socio-cultural factors of the Sundanese people.Keywords: community response, land function conversion factors, suburbs of the north of Bandung, land function conversion